The relationship between audit committee characteristics and earnings quality An Empirical Study on Banks listed on the Damascus Securities Exchange - عاصي أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to study the relationship between the characteristics of the audit committee and the quality of accounting profits of insurance companies operating in the Damascus Stock Exchange. To do so, the researcher collected data on the independent variable represented by the characteristics of the audit committee from the governance reports published on the website of the Syrian Securities and Financial Markets Authority. As well as data on the dependent variable represented by the quality of accounting profits through the financial statements and reports of insurance companies listed on the Damascus Stock Exchange and the Syrian Securities and Financial Markets Authority, which number 7 insurance companies during the period from 2009 to 2017. The data was studied through the program Views10.The study reached a set of results, the most important of which are:There is a statistically significant effect between the two characteristics of the independence of the audit committee and the number of audit committee meetings annually, on the quality of profits, while the relationship between the number of meetings of the audit committee with the external auditor, the availability of financial and accounting expertise in the audit committee and the variable of quality of profits as measured by the proximity to cash index, was insignificant. Statistical significance.